A gentle introduction to James’ weak compactness theorem and beyond - Moors, W. B. (Methods of Functional Analysis and Topology, 2019)
The purpose of this paper is twofold: firstly, to provide an accessible proof of James’ weak compactness theorem that is able to be taught in a first-year graduate class in functional analysis and secondly, to explore some of the latest and possible future extensions and applications of James’ theorem.